Exploring the subjective experience of the “rubber hand” illusion - Valenzuela Moguillansky, Camila; O'Regan, J.Kevin; Petitmengin, Claire (Frontiers in Human Neuroscience, 2013)
Despite the fact that the rubber hand illusion (RHI) is an experimental paradigm that has been widely used in the last 14 years to investigate different aspects of the sense of bodily self, very few studies have sought to investigate the subjective nature of the experience that the RHI evokes. The present study investigates the phenomenology of the RHI through a specific elicitation method. More particularly, this study aim at assessing whether the conditions usually used as control in the RHI have an impact in the sense of body ownership and at determining whether there are different stages in the emergence of the illusion. The results indicate that far from being 'all or nothing,' the illusion induced by the RHI protocol involves nuances in the type of perceptual changes that it creates. These perceptual changes affect not only the participants' perception of the rubber hand but also the perception of their real hand. In addition, perceptual effects may vary greatly between participants and, importantly, they evolve over time.